Cost-effectiveness of protein-rich meals and snacks for increasing protein intake in older adults - P. Rautakallio-Järvinen; S. Kunvik; M. Laaksonen; L. Fogelholm; I. Nykänen; U. Schwab (Elsevier, 2024)
Objectives: To investigate the cost-effectiveness of protein-rich meals and snacks for increasing protein intake in home-dwelling older adults. Design: Cost effectiveness analysis from a randomized controlled trial, the Power Meals study. Setting: Participants were randomized into one of three groups for eight weeks: a protein-rich meal, snack and bread (Protein), a regular meal (Normal) and a control group without meal service (Control). Participants: Home-dwelling home care clients, caregivers and care recipients aged ≥65 years (n = 65). Measurements: Protein intake was assessed by a three-day food diary at the end of the study. Cost for the daily diet was estimated by using Finnish grocery store databases and the prices of the food service. The cost-effectiveness was assessed by an incremental cost-effectiveness ratio (ICER). Results: Costs for the daily diet in the Protein (8.35 €/d) and the Normal (7.94 €/d) groups were significantly higher than in the control group (5.65 €/d) (p < 0.001). Incremental cost-effectiveness analysis showed that increasing protein intake was cost-effective in the Protein group as incremental cost-effectiveness ratio was 8.11 in the Protein, 8.72 in the Normal and 6.45 in the Control group. Conclusions: Including protein rich meals and snacks in a diet increases protein intake in home-dwelling older adults cost-effectively.